EFEKTIVITAS FUNGSI TAMAN KOTA SEBAGAI RUANG PUBLIK DI KOTA SAMARINDA PADA MASA PANDEMI COVID-19 - Lisa Astria; Rusdi Doviyanto (Jurnal Arsitektur ARCADE, 2023)
Abstract: The existence of city parks is not only an aesthetic function and the beauty of the city, but other functions such as socio-cultural and ecological for humans. During the COVID-19 pandemic, some people still choose to reduce activities outside the home, this has an impact on closing city parks during the pandemic to suppress the spread of COVID-19. So that in assessing the function of city parks, the main function parameters are ecological functions, socio-cultural functions, economic functions and aesthetic functions. The purpose of this research is to find out and examine the effectiveness of the function of city parks as an alternative entertainment for urban communities in the city of Samarinda. For the stages of research analysis, namely descriptive analysis and scoring analysis using a Likert scale. Overall, the effectiveness level of Mahakam Lantern Park for socio-cultural functions is 2.5, economic function is 2.4 and ecological function is 2.6 which is considered effective compared to aesthetic function of 2.3 which is quite effective. Meanwhile, in Taman Ujung Baru (Taman Bebaya) the socio-cultural function of 2.5 is considered effective, the economic function of 2.4 and the ecological function of 2.4 is quite effective, while the economic function of 1 is considered ineffective. The reason is, during the pandemic, community activities are limited in green open spaces and maintain health protocols.Abstrak: Keberadaan taman kota bukan hanya fungsi estetika dan keindahan kota, tetapi fungsi lain seperti sosial budaya dan ekologi bagi manusia. Di masa pandemi COVID-19, sebagian masyarakat masih memilih untuk mengurangi aktivitas di luar rumah, hal ini berdampak pada penutupan taman kota selama masa pandemi guna menekan penyebaran COVID-19. Sehingga dalam menilai fungsi taman kota, parameter fungsi utama adalah fungsi ekologis, fungsi sosial budaya, fungsi ekonomi dan fungsi estetika. Adapun tujuan dari penelitian ini adalah untuk mengetahui dan mengkaji efektivitas fungsi taman kota sebagai alternatif hiburan masyarakat perkotaan di kota Samarinda. Untuk tahapan analisis penelitian yaitu analisis deskriptif dan analisis skoring menggunakan skala likert. Secara keseluruhan, tingkat efektivitas Taman Lampion Mahakam untuk fungsi sosial budaya sebesar 2,5, fungsi ekonomi sebesar 2,4 dan fungsi ekologis sebesar 2,6 yang dianggap efektif dibandingkan dengan fungsi estetika sebesar 2,3 yang cukup efektif. Sedangkan di Taman Ujung Baru (Taman Bebaya) untuk fungsi sosial budaya sebesar 2,5 dinilai efektif, fungsi ekonomi sebesar 2,4 dan fungsi ekologi sebesar 2,4 cukup efektif, sedangkan fungsi ekonomi sebesar 1 dianggap tidak efektif. Pasalnya, selama masa pandemi, aktivitas masyarakat dibatasi di ruang terbuka hijau dan tetap menjaga protokol kesehatan.